2017
DOI: 10.1111/asj.12914
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of female reproductive parameters in the Kunming dog

Abstract: The Kunming dog is the first and only working dog breed from China to be recognized worldwide. As a domestic working dog, its excellent working performance has been well established; however, its normal reproductive parameters are not well understood. Therefore, this study was conducted to document the main reproductive parameters of this purebred working dog in field breeding conditions. Data on 1004 heats (753 with mating) from 203 bitches between 2008 to 2014, were collected and analyzed. The pregnancy rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, there are few data regarding factors that influence puppy relative growth rate. Although domestic dogs are considered non-seasonal breeders, seasonal effects on the reproductive performance of bitches remain contradictory (Wei et al 2018). Studies failed to demonstrate a season influence on litter size (Borge et al 2011;Wigham et al 2017), but, to the authors' knowledge, no influence on growth rate has been previously examined.…”
Section: Introductionmentioning
confidence: 83%
“…However, there are few data regarding factors that influence puppy relative growth rate. Although domestic dogs are considered non-seasonal breeders, seasonal effects on the reproductive performance of bitches remain contradictory (Wei et al 2018). Studies failed to demonstrate a season influence on litter size (Borge et al 2011;Wigham et al 2017), but, to the authors' knowledge, no influence on growth rate has been previously examined.…”
Section: Introductionmentioning
confidence: 83%
“…Inbreeding may affect many traits including birth weight [32] and litter size [33] in domestic animal species. In the present study, PBW was only marginally influenced by the inbreeding coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs have unique reproductive characteristics compared with other mammals. They are non-seasonal and monoestrus animals, and their estrus interval is longer than that of other animals [ 5 ]. It has also been reported that oocytes ovulate in the metaphase I stage and mature into the metaphase II stage in the fallopian tube, and that there is heterogeneity in oocyte maturation in dogs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%